Referendum study 1994 - Holmberg, Sören; Gilljam, Mikael; Statistics Sweden (University of Gothenburg, 1997)
In conjunction with the referendum on Swedish membership of the European Union (EU) an election study was carried out in collaboration between Statistics Sweden and the Department of Political Science at Göteborg University. All interviews were carried out before the day of the referendum, November 13 1994.

The interview included questions on how much the respondent had been taking part of EU-issues in daily papers; political interest in general and interest in the EU-issue in particular; opinion on the EU, and if there had been some changes in the opinion during the last year. For all political parties the respondent had to state if the party supported ´yes´ or ´no´ in the referendum, and furthermore the respondent had to place the parties on a scale ranging from ´very negative´ to ´very positive´ towards a Swedish membership of the European Union. Other questions dealt with how a Swedish membership of the EU should affect a number of fields; opinion on a European federal state; and opinion on referenda in general. A number of questions dealt with the respondent´s knowledge of EU; probable outcome of the Swedish and Norwegian referenda respectively, and knowledge of the actual outcome of the Finnish referendum; attitudes towards EU among the surroundings, and the importance of other people´s attitudes and arguing for one´s own attitude; and how one plans to vote in the referendum. Besides the EU-specific questions the interview included questions on attitudes toward the various political parties; opinion on a number of topical questions; confidence in Swedish politicians; type of society one ought to go in for in the future; activities to influence political decisions; and own experiences of the tightening Swedish labour market. There are also information about education, occupation, trade union affiliation, marital status, and knowledge of languages. After the referendum the respondent had to answer a mail questionnaire, including questions on actual vote; when one decided how to vote; if one had been watching the concluding TV debate; and if the attitude towards a Swedish membership had been altered during the campaign.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

I samband med folkomröstningen om svenskt medlemskap i den europeiska unionen, EU, genomfördes en valundersökning i samarbete mellan SCB och statsvetenskapliga institutionen vid Göteborgs universitet. Samtliga intervjuer genomfördes före dagen för folkomröstning den 13 november.

Intervjun innehöll frågor om hur mycket man tagit del av EU-frågor i dagstidningar; politiskt intresse och intresse för EU-frågan; åsikt i EU-frågan samt om inställningen förändrats under senaste året. Respondenten fick ange vilket alternativ i folkomröstningen de olika politiska partierna stöder samt på en skala 'mycket negativ-mycket positiv' placera partierna efter deras inställning i EU-frågan. Andra frågor handlade om vad ett svenskt medlemskap i EU skulle innebära inom olika områden, vilken inställning man har till en europeisk förbundsstat och inställning till folkomröstningar. Ett antal frågor berörde respondentens kunskap om EU; vilken sida man tror kommer att vinna i Sverige respektive Norge och vilken sida som fick flest röster i Finland; omgivningens ställningstagande i EU-frågan och vilken betydelse andras ställningstagande och argumentering haft för det egna ställningstagandet; samt hur man tänker rösta i folkomröstningen. Förutom de EU-specifika frågorna innehöll intervjun även frågor om inställning till de olika politiska partierna; inställning i ett antal aktuella frågor; förtroende för svenska politiker; samhällstyp man bör satsa på i framtiden; aktiviteter för att påverka beslut i samhället; och egna erfarenheter av det försämrade läget på svensk arbetsmarknad. Bakgrundsfrågorna innehåller uppgifter om utbildning, sysselsättning, facklig organisationstillhörighet, civilstånd och språkkunskaper. Respondenterna fick i en enkät utsänd efter folkomröstningen bland annat ange hur man röstat, när man bestämde sig, om man sett slutdebatten i TV och om inställningen till svenskt medlemskap förändrats under kampanjen.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Folkomröstningsundersökningen 1994
FU94
Keywords: internal politics; inrikespolitik; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap